ANALISIS DESAIN DAN PERHITUNGAN LAMPU PENERANGAN JALAN BERBASIS KENYAMANAN DAN KEAMANAN - I Ketut Wijaya; I Made Mataram (Jurnal SPEKTRUM, 2020)
Street lighting is installed for the benefit of the community to help build a creativeeconomy. Street lights in the government's effort to create creativity help the family economy.The method used is counting the number of lights used on the road with a distance of 1500meters and giving road users a questionnaire of comfort and safety. Street lighting is analyzedin an egonomic way to achieve effective, comfortable, safe, healthy and efficient work. Theresults obtained are the light intensity of 12.799 Lux (fulfilling SNI-2008) and the comfort andsafety of 11.067 and 10,300 likes after improving conditions.